Perancangan Dan Implementasi Supply Chain Management Untuk Stok Dan Pemasaran Herbisida Pada UD. Anugrah Jaya Tani Dengan Bahasa Pemrograman PHP Dan Database MySQL - Fitri Amelia Sari Lubis; Surmayanti Surmayanti; Mutiana Pratiwi (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2024)
Advances in information and communication technology are growing rapidly in all directions so that a lot of information is produced from technology and is applied in various fields. In the field of information technology, Supply Chain Management is also needed, which is used to monitor inventory and marketing of goods at UD. Anugrah Jaya Tani. UD. Anugrah Jaya Tani is a kiosk that sells various herbicides. Supply chain management (SCM) is one part that can also be developed with the existence of internet resources. The internet can play a role in facilitating SCM activities. This is because SCM activities require communication between the parties involved in this matter. The purpose of using supply chain management, where the most basic is to be able to align customer demand with existing supply. The results of this study are to determine the amount of stock of goods to be marketed, create a system that can be accessed by anyone, and create an attractive consultation layout.